Geografía económica, neoliberalismo y ecología política del desarrollo - de Oliveira, Leandro Dias; John Dairo Zapata Ochoa; Mariana Traldi; Victor Tinoco Souza (Geografares, 2024)
Geografía económica, neoliberalismo y ecología política del desarrollo.